Perceptions of barriers and facilitators to reducing exposure to secondhand smoke in the home: a qualitative study with Palestinian-Arab women in Israel - Agbaria, Nisreen; Finkelstein, Adi; Zwas, Donna R; Daoud, Nihaya (Nicotine & tobacco research, 2024)
Smoking is a collective and complex problem in the Palestinian-Arab community in Israel, where women and children are particularly vulnerable to exposure to secondhand smoke (SHS), especially in the home.We undertook this study to better understand women’s experiences with SHS exposure in the home and to identify pathways for intervention. Using the grounded theory approach, seven focus groups were conducted with 66 women in different localities across Israel. Purposive and snowball sampling techniques were applied to recruit women who have currently or previously been exposed to smoking in the home. Focus groups were audio-recorded and transcribed verbatim, and data were then coded and analyzed using the constant comparison analysis method to identify emergent themes and subthemes.Three core themes emerged from the discussions. These include women’s perceptions of smoking among men and exposure to SHS in the home, the implications of smoking on spousal and social relationships, and the women’s experiences in coping with this situation and their suggestions for interventions. We identified additional sub-themes, including the consequences to women’s and children’s health, as well as the complex interaction between smoking in the home and women’s social position, agency, and home ownership.Women exposed to SHS in the home experience consequences that affect their health and their spousal and social relationships. They also face several personal and societal challenges in tackling this issue. Culturally tailored interventions targeting both communities and households can raise awareness and impact smoking behaviors in the home.The findings of this study demonstrate the far-reaching consequences of SHS exposure in the home among women who are exposed. The findings contribute to our understanding of smoking contingencies among men and smoking behaviors in the home. This study lays the groundwork for future community and household-based research and interventions. We suggest several critical junctures that may increase response to smoking cessation interventions and to reduce smoking in the home, such as at the time of marriage when the home policy is set, and the adverse effects of exposure on children and other family members, especially those with illness.
Gesehen am 12.03.2024